Growth and nutrition in pediatric neuromuscular disorders. Issue 6 (June 2021) - Chou, Elle; Lindeback, Rachel; D'Silva, Arlene M.; Sampaio, Hugo; Neville, Kristen; Farrar, Michelle A.
Summary: Background & aims: Little is currently known about the nutrition and growth outcomes in children with neuromuscular disorders (NMDs), and these are likely disease dependent. The aim of this study was to describe the range of nutritional issues in pediatric NMDs and identify similarities and differences in growth outcomes and nutritional needs in children with a variety of NMDs at different ages, with the goal of informing future services. Methods: In this cross-sectional study we collected data on growth, dietetic interventions and nutrition-related issues in 160 children who attended a multidisciplinary clinic in a tertiary children's hospital, from February to December 2019. Children with significant weakness affecting mobility before the age of 3 years were clinically grouped into 'early-onset NMDs'. Results: Across our clinic, 42.5% children had a history of chronic gastrointestinal issues, and 34.4% received dietetic care on the day of clinical visit. Children with early-onset NMDs had significantly higher prevalence of swallowing issues, gastroesophageal reflux, and vomiting, as well as higher frequency of dietetic consultations, high energy diet, swallowing assessment and tube-feeding, compared to later-onset NMDs ( p  < 0.05). In total, 49.2% children with NMDs had an abnormal weight, in which the prevalence of underweight (n = 24, 19.2%) was significantly higher compared to normal Australian children (8.2%) ( p  < 0.05). In Duchenne muscular dystrophy, over 50% children were overweight/obese. Conclusion: Among children with NMDs, there were many disease-specific nutrition-related symptoms, growth issues, and dietetic practices that were tailored to individual needs. Future studies should focus on measuring the impact of specific dietetic practices on growth and nutritional outcomes, as well as developing a precision medicine approach tailored to the individual nutritional needs of children with NMDs. Highlights: Abnormal body mass index is common in children with neuromuscular disorders (NMDs), as seen in almost half our cohort. Chronic gastrointestinal problems are common in children with NMDs, as seen in 42.5% of our cohort. Children with early-onset rather than later-onset NMDs have more issues with swallowing and being underweight. Children with Duchenne muscular dystrophy are more likely to be overweight. A precision medicine approach is needed to optimise growth and nutritional outcomes of each patient.